2014
DOI: 10.5539/ibr.v7n2p64
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ownership Structure and Capital Structure on Financial Performance of Vietnamese Firms

Abstract: This article studies the impact of ownership structure and capital structure on firms' financial performance in context of an emerging transitional economy. According to research findings, capital structure has a negative impact with statistical significance on financial performance (measured by ROA, ROE). The higher level of state ownership in ownership structure of a firm is, the better financial performance it has. While clear evidences with statistical significance of the impact of managerial ownership on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
13
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
11
13
1
3
Order By: Relevance
“…A high liability ratio could also encourage better external supervision with positive effects on profit. Quang and Xin (2014) conducted an empirical study on the impact of the capital structure on the financial performance of the nonfinancial firms listed in Vietnam between2009 and 2012. The results showed that capital structure has a statistically significant negative effect on financial performance measured by ROA and ROE.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…A high liability ratio could also encourage better external supervision with positive effects on profit. Quang and Xin (2014) conducted an empirical study on the impact of the capital structure on the financial performance of the nonfinancial firms listed in Vietnam between2009 and 2012. The results showed that capital structure has a statistically significant negative effect on financial performance measured by ROA and ROE.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Twairesh (2014) found leverage have significant impact on firm’s performance. Quang and Xin (2014) found capital structure has a negative impact with statistical significance on firm’s financial performance. Wang (2003) reveals a positive relationship between ownership structure and firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the sampling technique was using probability sampling method with the saturated sampling technique. (Akeem et al, 2014;Chandra, 2015;Fauzi et al, 2013;Khan et al, 2013;Mirza & Javed, 2013;Quang & Xin, 2014) 7 Profitability = 100% Ratio (Chadha & Sharma, 2015;Ghi & Ba, 2015;Quang & Xin, 2014) 8…”
Section: Methodsmentioning
confidence: 99%
“…It can be inferred that the companies with the ability to produce more profit prefer using funding from the company's internal sources beside using funding from the company's external sources (loan). A study by (Quang & Xin, 2014) found that capital structure negatively influenced company's profitability. It is in line with the studies by (Akeem et al, 2014;Chadha & Sharma, 2015;Chen & Chen, 2011;Salim & Yadav, 2012).…”
Section: Capital Structurementioning
confidence: 99%